2020
DOI: 10.3389/fevo.2020.556379
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Metabolic Heat in Sea Turtle Nests and Methods to Model Its Impact on Hatching Success

Abstract: Just as organisms do not passively exist in their environment, developing sea turtle embryos affect their own incubation microclimate by producing metabolic heat and other waste products. This metabolic heat ultimately contributes to successful development, but it is unclear how it influences embryonic traits such as hatchling sex, and whether trends exist in the magnitude of metabolic heat produced by different species. In this systematic review, we document all empirical measurements of metabolic heat in sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 100 publications
1
10
0
Order By: Relevance
“…hatchling success), we assumed that metabolic heating within clutches averaged 1.1°C by the middle third of development (i.e. the period when sex is determined during incubation), as reported for hawksbill and green turtles in a recent review [ 17 ]. This value for metabolic heating was added to the mean monthly sand temperatures recorded at nest depths.…”
Section: Methodsmentioning
confidence: 99%
“…hatchling success), we assumed that metabolic heating within clutches averaged 1.1°C by the middle third of development (i.e. the period when sex is determined during incubation), as reported for hawksbill and green turtles in a recent review [ 17 ]. This value for metabolic heating was added to the mean monthly sand temperatures recorded at nest depths.…”
Section: Methodsmentioning
confidence: 99%
“…In this situation, we refrained from estimating the sex ratio of hatchlings and just calculated the proportion of clutches incubated at ≤28°C during the central third of incubation, because this is the lower threshold for the production of females (Mrosovsky et al ., 2002). Studies conducted on Mediterranean nesting beaches usually report no significant metabolic heating during the second third of incubation (Godley et al ., 2001; Zbinden, Margaritoulis & Arlettaz, 2006; Jribi & Bradai, 2014), contrary to the situation in other regions (Gammon et al ., 2020), but González‐Paredes et al . (2021) reported that metabolic heating increased the temperature of an isolated nest by 0.53°C.…”
Section: Methodsmentioning
confidence: 99%
“…, contrary to the situation in other regions(Gammon et al, 2020), but González-Paredes et al (2021 reported that metabolic heating increased the temperature of an isolated nest by 0.53°C. Accordingly, we calculated the average sand temperature during the central third of the incubation of clutches laid on July 1st, July 15th, and August 1st, considering that incubation lasts for 60 days, and then calculated the proportion of nests reaching the 28°C thresholds in the absence of any significant metabolic heating during the central third of incubation(Godley et al, 2001;Zbinden, Margaritoulis & Arlettaz, 2006; …”
mentioning
confidence: 86%
“…To estimate hatchling sex ratios, values for metabolic heating (MH) were added to the hindcasted and projected sand temperatures, to estimate nest temperature. We used values of MH equal to 0.5°C (conservative) and 1.1°C (moderate) to capture the likely variations in MH during the sex determination period (Gammon et al, 2020; Laloë et al, 2014; Patrício et al, 2017). The moderate MH estimate was the calculated average from the reported MH temperatures for green turtles during the middle‐third of embryonic development reviewed in Gammon et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…We used values of MH equal to 0.5°C (conservative) and 1.1°C (moderate) to capture the likely variations in MH during the sex determination period (Gammon et al, 2020; Laloë et al, 2014; Patrício et al, 2017). The moderate MH estimate was the calculated average from the reported MH temperatures for green turtles during the middle‐third of embryonic development reviewed in Gammon et al (2020). Using the modelled nest temperatures, we estimated the primary hatchling sex ratio of both species for each nesting season using a standardised logistic model described by Hays et al (2017), which assumes a PT = 29.1°C and a transitional range in temperatures (TRT) = 26–32°C.…”
Section: Methodsmentioning
confidence: 99%